Manajemen Perencanaan Pendidikan Islam Menurut Al-Qur’an - Nasution, Buyung Saroha (JURNAL ILMIAH GEMA PERENCANA, 2022)
Management is a systematic science to understand why and how humans work together to produce something useful for other people and certain groups and society in general. The functions of management according to experts vary, but from all experts who argue about the function of management there are similarities. In this paper, the author describes the function of planning management in Islamic education. In the Qur’an there are lafad whose meaning is commensurate with management, namely lafad of which lafad (yudabbiru) in Surah Yunus/10:3 which means to regulate, that Allah is in control of everything that happens on this earth. The word planning is not found in qath’iyah (clear) lafad in the Qur’an, but many verses of the Qur’an that talk about lafad that are commensurate with the Qur’an, by definition educational planning is an effort that is systematically arranged in various ways to achieve future goals with pay attention to the economic, socio-cultural and overall fields of a country.